Social theory and education research : understanding Foucault, Habermas, Bourdieu and Derrida - Murphy, Mark (New York : Routledge, 2022)
"Social Theory and Education Research is an advanced and accessible text that illustrates the diverse ways in which social theories can be applied to educational research methodologies. It provides in-depth overviews of the various theories by well-known and much-debated thinkers - Michel Foucault, Jürgen Habermas, Pierre Bourdieu and Jacques Derrida, and their applications in educational research. Updated throughout and with new extended introductions to each theorist and a new chapter on the application of socio-theoretical concepts in education research methodologies and the how-to of research practice, this second edition assists education practitioners and researchers in their acquisition and application of social theory. This book contextualizes the various theories within the broader context of social philosophy and the historical development of different forms of thought. Social Theory and Educational Research will be incredibly useful to post-graduate students and early career researchers who wish to develop their capacity to engage with these debates at an advanced level. It will also prove of great interest to anyone involved in education policy and theory"--
First edition: 2013.
Includes bibliographical references and index.
English.
Keywords: Educational sociology